Optical Radiation Protection by Non-Prescription Sunglasses - Chou, B.R.; Cullen, A.P. (Canadian Journal of Optometry, 2021)
We present spectral transmittance curves over the waveband 200 to 2500 nm for 47 non-prescription sunglass lenses. All appear to provide adequate protection from ultraviolet radiation, especially those which have been advertised as such. Other criteria for choosing the "right" sunglass are discussed briefly.